Capacitor element, solid electrolytic capacitor, and manufacturing method of solid electrolytic capacitor
By incorporating a higher density of cracks in the first region of the solid electrolyte layer of the capacitor element, the adhesion and permeability are enhanced, addressing the challenges of ESR variation and capacitor capacity in existing solid electrolytic capacitors.
Patent Information
- Application Number
- JP2024112265
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-08
- Filing Date
- 2024-07-12
- Publication Date
- 2025-03-21
AI Technical Summary
Existing solid electrolytic capacitors face challenges in improving adhesion and permeability between the anode body and the solid electrolyte layer, leading to variations in ESR during high temperature reliability tests and potential issues with capacitor capacity.
The capacitor element features a flat anode body with a porous layer and a dielectric layer, where a solid electrolyte layer is formed with a higher density of cracks in the first region compared to the second region, enhancing the anchor effect and permeability.
This configuration improves the bonding strength between the anode body and the solid electrolyte layer, suppresses ESR changes during high temperature tests, and ensures the desired capacitor capacity is achieved.
Smart Images

Figure 2025039520000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a capacitor element, a solid electrolytic capacitor including the capacitor element, and a method for manufacturing the solid electrolytic capacitor. [Background technology]
[0002] Conventionally, solid electrolytic capacitors are formed by stacking a plurality of capacitor elements. Various structures have been considered for improving the adhesion between the dielectric layer formed on the anode foil and the solid electrolyte layer formed in contact with the dielectric layer in the capacitor element. The solid electrolyte layer is formed by immersing the anode foil on which the dielectric layer is formed in a treatment liquid for the solid electrolyte layer. At this time, the treatment liquid for the solid electrolyte layer is affected by gravity, orientation, and the like. That is, there is a possibility that there will be variations in the solid electrolyte layer, such as in some areas where the solid electrolyte layer is formed thinly and in other areas where the solid electrolyte layer is formed thickly.
[0003] In order to solve these problems, a configuration has been shown in which grooves are provided in the porous portion of the anode foil to improve the adhesion of the solid electrolyte layer and the permeability of the treatment solution to the solid electrolyte layer. Patent Documents 1 and 2 show a structure in which grooves parallel to the length direction and grooves perpendicular to the length direction are provided in the porous portion of the anode body (anode foil). The treatment solution for the solid electrolyte layer, which contains a conductive polymer, enters into the grooves. This improves the adhesion and permeability of the porous portion of the anode body and the solid electrolyte layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2022 / 009800 [Patent Document 2] Patent No. 5858802 Summary of the Invention [Problem to be solved by the invention]
[0005] The grooves in the structures of Patent Documents 1 and 2 are formed so as to be equally spaced or in a lattice pattern when the capacitor element is viewed in plan. That is, the grooves are formed without taking into consideration gravity or the direction when the solid electrolyte layer is formed on the capacitor element. Therefore, as with structures without grooves, it may be difficult to improve the adhesion and permeability between the anode body and the solid electrolyte layer. For this reason, the ESR change during high-temperature reliability testing may be large, and the desired capacitor capacitance may not be obtained.
[0006] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a solid electrolytic capacitor having improved bonding strength and high reliability. [Means for solving the problem]
[0007] The capacitor element of the present invention includes an anode body, a dielectric layer, and a solid electrolyte layer. The anode body includes a valve metal and has a porous layer having a plurality of holes on a surface of the valve metal. The anode body is in the form of a flat film. The dielectric layer is formed on at least a cathode formation region. The solid electrolyte layer is formed on the dielectric layer. The anode terminal region is a region of the anode body where the solid electrolyte layer is not formed. The cathode formation region has the solid electrolyte layer formed thereon.
[0008] The cathode region in the anode body has a first region on the surface and a second region adjacent to the first region. A predetermined number of cracks are formed in the first region and the second region. A first density occupied by the first cracks formed in the first region is greater than a second density occupied by the second cracks formed in the second region. The predetermined number includes a case where no cracks exist, and the second density may be zero. In addition, the cracks may be continuous or discontinuous as shown by the dashed lines.
[0009] In this configuration, the solid electrolyte layer penetrates into the first cracks formed in the first region and the second cracks formed in the second region. That is, the adhesion between the anode body and the solid electrolyte layer is improved by the anchor effect. In addition, since the first density is greater than the second density, the solid electrolyte layer penetrates into the first cracks in the first region where it is difficult to form the solid electrolyte layer, improving the permeability of the solid electrolyte layer. Therefore, the ESR change during the high-temperature reliability test can be suppressed, and the desired capacitor capacitance can be obtained.
[0010] The method for manufacturing a solid electrolytic capacitor of the present invention includes a capacitor element forming step, a first external electrode forming step, a second external electrode forming step, and a seal forming step.
[0011] In the capacitor element forming step, a capacitor element is formed having an anode body, a dielectric layer, an anode terminal region, and a cathode formation region. The anode body includes a valve metal and has a porous layer having a plurality of holes on the surface of the valve metal. The anode body is in the form of a flat membrane. The dielectric layer is formed on at least the cathode formation region. The solid electrolyte layer is formed on the dielectric layer. The anode terminal region is a region of the anode body where the solid electrolyte layer is not formed. The solid electrolyte layer is formed in the cathode formation region.
[0012] In the first external electrode forming step, a first external electrode is formed to be connected to an end of the anode terminal region. In the second external electrode forming step, a second external electrode is formed to be connected to the cathode formation region. In the sealing body forming step, a sealing body is formed by stacking a plurality of capacitor elements and sealing them with insulating resin, the sealing body having a first surface from which the end of the anode terminal region is linearly exposed.
[0013] In addition, the capacitor element forming step forms a predetermined number of cracks in a first region on the surface of the anode body and in a second region adjacent to the first region, the first cracks being formed in the first region such that a first density occupied by the first cracks formed in the first region is greater than a second density occupied by the second cracks formed in the second region.
[0014] This manufacturing method can provide a solid electrolytic capacitor in which the solid electrolyte layer penetrates into the first cracks formed in the first region and the second cracks formed in the second region in the cathode region of the anode body. In the first and second cracks, the adhesion between the anode body and the solid electrolyte layer is improved by the anchor effect. In addition, since the first density is greater than the second density, the solid electrolyte layer penetrates into the first cracks in the first region where it is difficult to form, improving the permeability of the solid electrolyte layer. Therefore, the ESR change during high-temperature reliability testing can be suppressed, and the desired capacitor capacitance can be obtained. Effect of the Invention
[0015] According to the present invention, it is possible to provide a solid electrolytic capacitor having improved bonding strength and high reliability. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a cross-sectional view of the solid electrolytic capacitor according to the first embodiment. [Diagram 2] FIG. 2(A) is an enlarged view of a portion of the capacitor element according to the first embodiment, and FIG. 2(B) is a cross-sectional view of the capacitor element. [Diagram 3] 3(A) and 3(B) are enlarged views showing the configuration of the capacitor element according to the first embodiment. [Figure 4] 4(A) and 4(B) are cross-sectional views of the capacitor element according to the first embodiment. [Diagram 5] FIG. 5 is a flowchart showing a procedure for forming the capacitor element according to the first embodiment. [Figure 6] FIG. 6 is a flowchart showing a procedure for forming the solid electrolytic capacitor according to the first embodiment. [Figure 7] FIG. 7 is a cross-sectional view of the capacitor element according to the second embodiment. [Figure 8] 8(A), 8(B), 8(C) and 8(D) are enlarged views showing the configuration of a capacitor element according to a modified example. [Figure 9] FIG. 9 is a table comparing the maximum thickness, capacitance, and ESR change rate of the solid electrolyte layer of the capacitor element, Comparative Example 1, and Comparative Example 2. [Figure 10] 10(A) and 10(B) are enlarged views showing the configurations of the capacitor elements of Comparative Examples 1 and 2. FIG. [Figure 11] 11(A) and 11(B) are cross-sectional views of a solid electrolytic capacitor in accordance with the first modification. [Figure 12] FIG. 12 is an enlarged view of a portion of the capacitor element according to the second modification. [Figure 13] FIG. 13 is an enlarged view of a portion of the capacitor element according to the third modification. [Figure 14] FIG. 14 is an enlarged view of a portion of the capacitor element according to the fourth modification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] [First embodiment] A solid electrolytic capacitor 1 according to a first embodiment of the present invention will be described with reference to the drawings. Fig. 1 is a cross-sectional view of the solid electrolytic capacitor 1 according to the first embodiment.
[0018] (Structure of solid electrolytic capacitor) The solid electrolytic capacitor 1 includes a capacitor assembly 10, a first external electrode 20, a second external electrode 30, and an insulating resin body 40.
[0019] The capacitor assembly 10 includes a plurality of capacitor elements 11 and a conductive member 19. The conductive member 19 is preferably an electrode paste containing, for example, nickel, silver, or copper as a main component. The maximum thickness of the conductive member 19 is preferably 2 μm or more and 20 μm or less. Note that, if a conductivity equal to or higher than a desired conductivity can be obtained between the plurality of capacitor elements 11 without using the conductive member 19, it is possible to omit the conductive member 19.
[0020] In this embodiment, the number of capacitor elements 11 constituting capacitor assembly 10 is not limited as long as it is plural. The structure of capacitor element 11 will be described in detail later.
[0021] The plurality of capacitor elements 11 are stacked. A capacitor assembly 10 (laminate) is formed by stacking the plurality of capacitor elements 11. At this time, the plurality of capacitor elements 11 are formed so as to be approximately parallel to each other.
[0022] The capacitor assembly 10 is sealed with an insulating resin body 40. This forms a sealing body 400. The sealing body 400 has a generally rectangular parallelepiped shape having a top surface 401, a bottom surface 402, a first surface 403, and a second surface 404. As described below, the surface on which the first external electrode 20 is formed by extending from the first surface 403 and the surface on which the second external electrode 30 is formed by extending from the second surface 404 are referred to as the bottom surface 402 for the sake of convenience, and the surface facing away from the bottom surface 402 is referred to as the top surface 401.
[0023] At this time, some of the multiple capacitor elements 11 are exposed from first surface 403 of sealing body 400. The surface (first surface 403) where the multiple capacitor elements 11 are linearly exposed from insulating resin body 40 is connected to first external electrode 20.
[0024] The first external electrode 20 is formed along the sealing body 400. Specifically, the first external electrode 20 is disposed across the first surface 403 and the bottom surface 402.
[0025] The first external electrode 20 is made of, for example, a copper alloy material or an iron alloy material, and is formed of, for example, a material cut out from a metal plate.
[0026] The first external electrode 20 is preferably made of a metal material that is easy to bend and has high conductivity. In this case, the first external electrode 20 is preferably arranged so as to be bent along the first surface 403 and the bottom surface 402 of the sealing body 400.
[0027] The second external electrode 30 is formed along the sealing body 400. Specifically, the second external electrode 30 is disposed across the second surface 404 and the bottom surface 402. The capacitor element 11 and the second external electrode are joined by a conductive adhesive 50 made of silver paste or the like.
[0028] The connection layers (conductive layers including solid electrolyte layer 113) of the multiple capacitor elements 11 are electrically and physically connected to second external electrode 30 by conductive adhesive 50.
[0029] The second external electrode 30 is preferably formed of a metal material that is easy to bend and has high conductivity, such as a copper alloy material or an iron alloy material. The second external electrode 30 is formed of a material cut out from a metal plate, for example. The first external electrode 20 and the second external electrode 30 may be made of the same material or different materials.
[0030] The insulating resin body 40 is mainly made of resin and may contain a filler. As the resin, for example, epoxy resin, phenol resin, polyimide resin, silicone resin, polyamide resin, liquid crystal polymer, etc. are preferable. The resin may be in the form of either solid resin or liquid resin. It is preferable that the corners are rounded by barrel polishing after the resin sealing. As the filler, for example, silica particles, alumina particles, etc. are preferable. The maximum diameter of the filler is preferably, for example, 30 μm or more and 40 μm or less. It is more preferable that the material contains silica particles in solid epoxy resin and phenol resin.
[0031] (Capacitor element structure) The structure of capacitor element 11 will be described in more detail with reference to FIGS. 2(A), 2(B), 3(A), 3(B), 4(A) and 4(B).
[0032] Fig. 2(A) is an enlarged view of a portion of capacitor element 11 according to the first embodiment, and Fig. 2(B) is a cross-sectional view of capacitor element 11. Figs. 3(A) and 3(B) are enlarged views of the configuration of capacitor element 11 according to the first embodiment. Figs. 4(A) and 4(B) are cross-sectional views of capacitor element 11 according to the first embodiment.
[0033] Capacitor element 11 includes electrode foil 111, dielectric layer 112, solid electrolyte layer 113, carbon layer 114, and metal layer 115. Electrode foil 111 includes electrode layer 111F and porous layer 111L.
[0034] A more specific structure of the electrode foil 111 is as follows. The electrode layer 111F is made of, for example, a simple metal such as aluminum, tantalum, niobium, titanium, zirconium, magnesium, silicon, or an alloy containing these metals. The electrode layer 111F is preferably made of aluminum or an aluminum alloy. A porous layer 111L is formed on the surface portion of the electrode layer 111F. The porous layer 111L is formed by etching the surface of the electrode layer 111F. This makes the porous layer 111L a porous body. The electrode foil 111 may be a valve action metal that exhibits a so-called valve action. A more detailed structure of the electrode foil 111 will be described later.
[0035] The electrode foil 111 has a dielectric layer 112 formed thereon. The dielectric layer 112 is formed on the entire surface of the porous layer 111L, which is a porous body. As shown in FIG. 2(A) and FIG. 2(B), the electrode foil 111 has a first face F1 and a second face F2 that face each other in the Z-axis direction. The electrode foil 111 further has a third face F3, a fourth face F4, a fifth face F5, and a sixth face F6 that are connected to the first face F1 and the second face F2 and are parallel to the Z-axis direction. The third face F3 and the fourth face F4 are parallel to the Y-axis direction. The fifth face F5 and the sixth face F6 are parallel to the X-axis. The dielectric layer 112 covers the first face F1, the second face F2, the fourth face F4, the fifth face F5, and the sixth face F6 of the electrode foil 111.
[0036] The dielectric layer 112 is preferably made of an oxide film of the electrode foil 111 (porous layer 111L). When an aluminum foil is used for the electrode layer 111F, the dielectric layer 112 is formed by applying a voltage in an aqueous solution containing boric acid, phosphoric acid, adipic acid, or a sodium salt or ammonium salt thereof, and anodizing the same. The thickness of the dielectric layer 112 is preferably 10 nm or more and 100 nm or less.
[0037] Solid electrolyte layer 113 covers the outer surface of dielectric layer 112 (at least the surface opposite to the surface in contact with electrode foil 111). Solid electrolyte layer 113 is also filled in a large number of pores covered with dielectric layer 112.
[0038] More specifically, the solid electrolyte layer 113 includes, for example, an inner layer and an outer layer.
[0039] The inner layer is a layer on the dielectric layer 112 side of the solid electrolyte layer 113, and may be, for example, a PEDOT:PSS layer realized by a conductive polymer having a skeleton of pyrroles, thiophenes, anilines, or the like, or a conductive polymer having a skeleton of thiophenes, such as PEDOT [poly(3,4-ethylenedioxythiophene)], and complexed with polystyrene sulfonic acid (PSS) as a dopant. The inner layer is formed by a method of forming a polymer film of poly(3,4-ethylenedioxythiophene) or the like on the surface of the dielectric layer 112 using an electrolyte solution serving as a base for forming the solid electrolyte layer 113, for example, a treatment liquid containing a monomer such as 3,4-ethylenedioxythiophene, or a method of applying a dispersion of a polymer such as poly(3,4-ethylenedioxythiophene) to the surface of the dielectric part and drying it, or the like.
[0040] The outer layer is a layer formed on the outside of the inner layer. For example, the outer layer is a layer formed so as to cover the entire surface of the inner layer after the inner layer is formed to fill the fine recesses of the porous portion. The thickness of the outer layer is preferably 2 μm or more and 20 μm or less. The outer layer is formed by a method of forming a polymer film of poly(3,4-ethylenedioxythiophene) or the like on the surface of the inner layer using an electrolyte solution that is the base for forming the solid electrolyte layer 113, for example, a treatment liquid containing a monomer such as 3,4-ethylenedioxythiophene, or a method of applying a dispersion or paste of a polymer such as poly(3,4-ethylenedioxythiophene) to the surface of the inner layer portion and drying it, or the like.
[0041] The carbon layer 114 is formed so as to cover the outer layer (solid electrolyte layer 113). The carbon layer 114 is formed by applying a conductive paste in which an insulating resin such as a phenolic resin is mixed with carbon or graphene particles.
[0042] Metal layer 115 is formed so as to cover carbon layer 114. Metal layer 115 is formed, for example, by applying a silver paste containing silver particles and polypropylene resin.
[0043] With this configuration, capacitor element 11 becomes a flat-film solid electrolytic capacitor. In this capacitor element 11, electrode foil 111 corresponds to the anode, and metal layer 115 corresponds to the cathode. A region of electrode foil 111 where solid electrolyte layer 113, carbon layer 114, and metal layer 115 are not formed corresponds to the "anode terminal region" of the present invention, and a region where solid electrolyte layer 113, carbon layer 114, and metal layer 115 are formed corresponds to the "cathode formation region" of the present invention. Electrode foil 111 corresponds to the "anode body" of the present invention.
[0044] (Detailed structure of capacitor element and electrode foil) Next, capacitor element 11 and electrode foil 111 of capacitor assembly 10 will be described in detail with reference to FIGS. 3(A), 3(B), 4(A) and 4(B).
[0045] 3(A) and 3(B), a predetermined number of cracks 100 are formed on the surface (first surface F1) of the electrode foil 111. Of the cracks 100, the cracks 100 formed in the first region R1 are referred to as first cracks 101, and the cracks 100 formed in the second region R2 are referred to as second cracks 102. The cracks 100 are formed on both the first surface F1 and the second surface F2 (the cracks 100 on the second surface F2 side are not shown).
[0046] The first cracks 101 in the first region R1 are formed to be denser than the second cracks 102 in the second region R2. In other words, the second cracks 102 in the second region R2 are formed to be sparser than the first cracks 101 in the first region R1. This sparse-dense relationship is achieved by forming the number of first cracks 101 formed in the first region R1 to be greater than the number of second cracks 102 formed in the second region R2.
[0047] The density of the first cracks 101 formed in the first region R1 is defined as a first density, and the density of the second cracks 102 formed in the second region R2 is defined as a second density. In this case, the first density is higher than the second density. Note that the structure in which a predetermined number of cracks 100 are formed includes a case in which no cracks 100 exist.
[0048] The first region R1 is a region close to the first external electrode 20 (the anode side of the solid electrolytic capacitor 1) in Fig. 1, in other words, a region close to the third face F3. On the other hand, the second region R2 is a region close to the second external electrode 30 (the cathode side of the solid electrolytic capacitor 1) in Fig. 2(A), in other words, a region close to the fourth face F4. The first region R1 and the second region R2 are adjacent to each other when the first face F1 is viewed in a plan view. Note that the first region R1 and the second region R2 do not have to be adjacent to each other.
[0049] Next, using Figures 4(A) and 4(B), the structure of electrode foil 111 cut along a plane parallel to the Z-axis direction is shown. As shown in Figures 4(A) and 4(B), cracks 100 are formed in electrode foil 111 to a predetermined depth. Dielectric layer 112 is formed on the surfaces of electrode foil 111 and cracks 100. Figures 4(A) and 4(B) show the structure in which cracks 100 are formed, and other structures are omitted. Also, Figure 4(B) shows the detailed structure of cracks 100, and the number of cracks 100 is different from that in Figure 4(A).
[0050] Furthermore, solid electrolyte layer 113 is formed so as to cover electrode foil 111 and dielectric layer 112. At this time, solid electrolyte layer 113 fills cracks 100 formed in electrode foil 111. In other words, cracks 100 are filled with solid electrolyte layer 113. That is, the anchor effect of cracks 100 improves the bonding strength between electrode foil 111 and solid electrolyte layer 113.
[0051] Here, the crack 100 is defined. The crack 100 is a crack-like or streak-like crack formed on the surface of the porous layer 111L of the electrode foil 111. In other words, the crack 100 is not a groove formed by physical excavation, but is formed without changing the volume of the porous layer 111L. The ratio of the area where the crack 100 is formed is calculated using the ratio of the projected area when the first surface F1 is viewed in the Z-axis direction (hereinafter, projected area ratio).
[0052] The projected area ratio is calculated as the proportion of the projected area where cracks 100 are formed, assuming that the area where cracks 100 are not formed on first surface F1 is 100. In this case, the projected area ratio where cracks 100 are formed is preferably about 5%. The projected area ratio is preferably at least about 3% or more and about 10% or less. This improves the bonding strength between electrode foil 111 and solid electrolyte layer 113 by solid electrolyte layer 113 penetrating into cracks 100 described above (anchor effect).
[0053] (Method of manufacturing capacitor element) Capacitor element 11 having the above-mentioned configuration is manufactured, for example, as follows: Fig. 5 is a flow chart showing an example of a schematic flow of a method for manufacturing a capacitor element according to this embodiment.
[0054] The porous layer 111L is formed on the electrode layer 111F (S11). More specifically, the porous layer 111L is formed by etching the surface of the electrode layer 111F.
[0055] Next, the cracks 100 are formed in the electrode foil 111 consisting of the electrode layer 111F and the porous layer 111L (S12). The cracks 100 are formed, for example, by using a heating and pressurizing device or the like to vary the pressure applied to the surface of the electrode foil 111 for each region, and locally applying a higher pressure than other regions. The depth of the cracks 100 may be within a range not exceeding the thickness of the porous layer 111L, and is preferably, for example, 10% to 80% of the porous layer 111L. The formation of the cracks 100 is not limited to the heating and pressurizing device, and may be any configuration that can form the cracks 100 in the electrode foil 111.
[0056] Next, dielectric layer 112 is formed on electrode foil 111 with cracks 100 formed therein (S13). At this time, dielectric layer 112 is formed by an oxide film of electrode foil 111 (porous layer 111L).
[0057] Next, the solid electrolyte layer 113 is formed so as to cover the dielectric layer 112 (S14). First, the inner solid electrolyte layer 113 (inner solid electrolyte layer) is formed so as to cover the dielectric layer 112. Furthermore, the outer solid electrolyte layer 113 (outer solid electrolyte layer) is formed so as to cover the inner solid electrolyte layer 113.
[0058] Next, carbon layer 114 is formed so as to cover outer solid electrolyte layer 113 (S15).
[0059] Next, a metal layer 115 is formed so as to cover the carbon layer 114 (S16).
[0060] In capacitor element 11 formed by the above-mentioned procedure, solid electrolyte layer 113 is formed so as to cover electrode foil 111 having crack 100. With this configuration, solid electrolyte layer 113 penetrates crack 100 formed in electrode foil 111. The anchor effect of crack 100 improves the bonding strength between electrode foil 111 and solid electrolyte layer 113.
[0061] In addition, in the process of forming solid electrolyte layer 113 in step S14, the electrode foil 111 is immersed in a processing solution for solid electrolyte layer 113 so that the first region R1 of the electrode foil 111 is at the top and the second region R2 is at the bottom, in other words, so that the direction from the first region R1 to the second region R2 is the direction of gravity.
[0062] In this case, the treatment solution for solid electrolyte layer 113 attached to electrode foil 111 sags down due to gravity. However, because of the structure having cracks 100, the treatment solution for solid electrolyte layer 113 enters cracks 100. That is, even in first region R1 where the treatment solution is difficult to sufficiently attach due to the effect of gravity, electrode foil 111 with improved permeability of solid electrolyte layer 113 can be formed. This allows a high capacitor capacitance to be obtained.
[0063] (Method of manufacturing solid electrolytic capacitor) Solid electrolytic capacitor 1 using capacitor element 11 having the above-mentioned configuration is formed as follows. Solid electrolytic capacitor 1 is manufactured, for example, as follows. Fig. 6 is a flow chart showing an example of a schematic flow of a method for manufacturing a solid electrolytic capacitor according to this embodiment.
[0064] 1, capacitor elements 11 are stacked to form capacitor assembly 10 (S21). When forming capacitor assembly 10, stacked capacitor elements 11 are heated and pressurized.
[0065] Next, as shown in FIG. 1, the capacitor assembly 10 is sealed with an insulating resin body 40 (S22).
[0066] Next, sealing body 400 is ground to expose electrode foil 111. In the anode formation region of capacitor assembly 10, first external electrode 20 is formed on the end face (first surface 403) of the anode region of capacitor assembly 10 (S23).
[0067] Next, as shown in FIG. 1, in the cathode formation region of the capacitor assembly 10, the end face (second surface 404) of the cathode region of the capacitor assembly 10 is joined to the second external electrode 30 using a conductive adhesive 50 such as silver paste (S24).
[0068] Next, the first external electrode 20 is bent along the first surface 403 and the bottom surface 402 of the sealing body 400. More specifically, the first external electrode 20 is bent along the bottom surface 402 of the sealing body 400. Similarly, the second external electrode 30 is bent along the second surface 404 and the bottom surface 402 of the sealing body 400 (S25).
[0069] In the above-described configuration, the lead frame (a configuration in which the terminal is drawn out to the outside by a conductive plate material) is formed after forming the sealing body 400. However, the sealing body 400 may be formed after forming the first external electrode 20 in step S23 and the second external electrode 30 in step S24.
[0070] In this manner, by using capacitor element 11 having a high bonding strength between electrode foil 111 and solid electrolyte layer 113, the change in ESR during high-temperature reliability testing can be suppressed.
[0071] [Second embodiment] A solid electrolytic capacitor 1A according to a second embodiment of the present invention will now be described with reference to Fig. 7. Fig. 7 is a cross-sectional view of the solid electrolytic capacitor 1A according to the second embodiment.
[0072] 7, the solid electrolytic capacitor 1A according to the second embodiment differs from the solid electrolytic capacitor 1 according to the first embodiment in that the cracks 100A have different depths. The other configurations of the solid electrolytic capacitor according to the second embodiment are similar to those of the solid electrolytic capacitor according to the first embodiment, and a description of similar parts will be omitted.
[0073] 7, the first crack 101A formed in the first region R1 is deeper in the Z-axis direction than the second crack 102A formed in the second region R1. More specifically, the depth d1 of the first crack 101A is deeper than the depth d2 of the second crack 102A.
[0074] That is, the first surface F1 has a first region R1 where the first cracks 101A are formed to a large depth d1, and a second region R2 where the second cracks 102A are formed to a depth d2 that is smaller than that of the first region R1. With this configuration, the first cracks 101A formed in the first region R1 are dense, and the second cracks 102A formed in the second region R2 are sparse.
[0075] That is, the difference between the capacitor element 11 of the first embodiment and the capacitor element 11A of the second embodiment is as follows. The capacitor element 11 of the first embodiment has a configuration in which the number of the first cracks 101 and the second cracks 102 are different in order to form a sparse-dense relationship between the first region R1 and the second region R2. On the other hand, in the capacitor element 11A of the second embodiment, the depth d1 of the first cracks 101A in the first region R1 is made deeper than the depth d2 of the second cracks 102A in the second region R2, so that the first region R1 is in a dense state and the second region is in a sparse state. Therefore, the first density in the first region R1 is higher than the second density in the second region R2.
[0076] Even in this configuration, in capacitor element 11A, the treatment liquid for dielectric layer 112 and solid electrolyte layer 113 penetrates into cracks 100A formed in electrode foil 111. More specifically, more treatment liquid for solid electrolyte layer 113 penetrates into first cracks 101A formed in first region R1 than into second cracks 102A formed in second region R2. That is, the anchor effect of cracks 100A improves the bonding strength between electrode foil 111 and solid electrolyte layer 113.
[0077] Moreover, even in first region R1 of solid electrolyte layer 113 to which a treatment liquid is unlikely to adhere sufficiently, electrode foil 111 with improved permeability of solid electrolyte layer 113 can be formed.
[0078] [Other embodiments] 8(A), 8(B), 8(C) and 8(D) are diagrams showing other structures of cracks 100 formed in electrode foil 111. FIG.
[0079] In FIG. 8(A), the cracks 100 (first cracks 101) are formed only in the position close to the fourth surface F4, which is the first region R1. More specifically, the cracks 100 (first cracks 101) are formed in a concentrated manner at a corner where the fourth surface F4 and the fifth surface F5 intersect in a plan view of the electrode foil 111, and at a corner where the fourth surface F4 and the sixth surface F6 intersect in a plan view of the electrode foil 111. The cracks 100 are formed at a predetermined angle (greater than 0° and smaller than 90°) with respect to the fourth surface F4 and the fifth surface F5 in a plan view. Similarly, the cracks 100 are formed at a predetermined angle (greater than 0° and smaller than 90°) with respect to the fourth surface F4 and the sixth surface F6 in a plan view.
[0080] Moreover, the crack 100 (second crack 102) is not formed in a position close to the third surface F3, which is the second region R2.
[0081] In this case, the cracks 100 in the first region R1 are densely formed, whereas the cracks 100 in the second region R2 are sparsely formed compared to the first region R1.
[0082] As described above, the formation of cracks 100 makes it easier for the treatment liquid for solid electrolyte layer 113 to accumulate at the corners where the fourth surface F4 and the fifth surface F5 intersect and at the corners where the fourth surface F4 and the sixth surface F6 intersect in a plan view of electrode foil 111. This solves the problem of the solid electrolyte layer 113 being difficult to adhere to these corners when cracks 100 are not formed, and allows solid electrolyte layer 113 to be formed uniformly.
[0083] In FIG. 8(B), the cracks 100 are formed so as to be parallel to the third surface F3 and the fourth surface F4. In this case, the number of first cracks 101 formed in a position close to the third surface F3, which is the first region R1, is large. In addition, the intervals at which the first cracks 101 are formed are also narrow. Furthermore, the number of second cracks 102 formed in a position close to the fourth surface F4 is small compared to the first region R1. In addition, the intervals at which the second cracks 102 are formed are also wide compared to the first region.
[0084] Even in this case, the first cracks 101 in the first region R1 are formed in a dense state, whereas the second cracks 102 in the second region R2 are formed in a sparse state compared to the first region R1.
[0085] In FIG. 8C, the region close to the fifth face F5 in the width direction of electrode foil 111 is first region R1, and the region close to the sixth face F6 is second region R2.
[0086] In FIG. 8(C), the cracks 100 are formed so as to be parallel to the fifth face F5 and the sixth face F6. In this case, the number of first cracks 101 formed in a position close to the fifth face F5, which is the first region R1, is large. In addition, the intervals at which the first cracks 101 are formed are also narrow. Furthermore, the number of second cracks 102 formed in a position close to the sixth face F6, which is the second region R2, is small compared to the first region R1. In addition, the intervals at which the second cracks 102 are formed are also wide compared to the first region.
[0087] Even in this case, the first cracks 101 in the first region R1 are formed in a dense state, whereas the second cracks 102 in the second region R2 are formed in a sparse state compared to the first region R1.
[0088] 8(D), the regions close to the fifth face F5 and the sixth face F in the width direction of electrode foil 111 are first region R1, and the central portion in the width direction is second region R2. In the width direction of electrode foil 111, second region R2 is sandwiched between two first regions R1.
[0089] In Fig. 8(D), the cracks 100 are formed so as to be parallel to the fifth face F5 and the sixth face F6. In this case, the number of first cracks 101 formed in positions close to the fifth face F5 and the sixth face F6, which are the first region R1, is large. In addition, the intervals at which the first cracks 101 are formed are also narrow. Furthermore, the number of second cracks 102 formed in the approximate center of the second region R2 of the electrode foil 111 is small compared to the first region R1. In addition, the intervals at which the second cracks 102 are formed are also wide compared to the first region.
[0090] Even in this case, the first cracks 101 in the first region R1 are formed in a dense state, whereas the second cracks 102 in the second region R2 are formed in a sparse state compared to the first region R1.
[0091] Even with this configuration, dielectric layer 112 and solid electrolyte layer 113 penetrate into cracks 100 formed in electrode foil 111. That is, the anchor effect of cracks 100 improves the bonding strength between electrode foil 111 and solid electrolyte layer 113.
[0092] Moreover, even in first region R1 where the treatment liquid is unlikely to adhere sufficiently, electrode foil 111 with solid electrolyte layer 113 having improved permeability can be formed.
[0093] Although not shown, in the state of FIG. 8(D), the second region R2 may be shaped to surround the first region R1 in a substantially annular shape. More specifically, the first region R1 (region with dense cracks) may be formed in the center of the electrode foil 111, and the second region R2 (region with sparse cracks) may be formed in the peripheral portion close to the third face F3, the fourth face F4, the fifth face F5, and the sixth face F6. In this case, it is possible to suppress the coffee stain phenomenon after the treatment liquid for the solid electrolyte layer 113 is applied. This allows the thickness of the solid electrolyte layer 113 to be made uniform.
[0094] [Comparison of specific numerical examples] Next, a solid electrolytic capacitor formed using the above-mentioned configuration will be compared with a solid electrolytic capacitor having a conventional configuration using specific numerical examples. Fig. 9 is a table comparing the maximum thickness, capacitance, and ESR change rate of the solid electrolyte layer of the capacitor element with Comparative Example 1 and Comparative Example 2. Fig. 10(A) and Fig. 10(B) are enlarged views showing the configurations of the capacitor elements of Comparative Example 1 and Comparative Example 2.
[0095] The configuration of the first embodiment is the configuration of solid electrolytic capacitor 1. Comparative example 1 is the structure of Fig. 10(A). Comparative example 1 is a structure in which no cracks are formed in electrode foil 111. Comparative example 2 is the structure of Fig. 10(B). Comparative example 2 is a structure in which cracks are formed at equal intervals parallel to third face F3 and fourth face F4.
[0096] 9 shows the results of comparing the maximum thickness, capacitance, and ESR change rate of the solid electrolyte layer of solid electrolytic capacitor 1 of the first embodiment, a solid electrolytic capacitor using the capacitor element of comparative example 1, and a solid electrolytic capacitor using the capacitor element of comparative example 2. Note that this experiment was performed with the target thickness of the solid electrolyte layer set to 10 μm.
[0097] The maximum thickness of the solid electrolyte layer 113 of the solid electrolytic capacitor 1 in the first embodiment was 10 μm. The thickness variation was small. That is, the solid electrolytic capacitor 1 in the first embodiment was able to achieve a thickness that was approximately the same as the target value. This is presumably because, when the treatment solution for the solid electrolyte layer 113 was applied to the electrode foil 111 to form the solid electrolyte layer 113, the treatment solution for the solid electrolyte layer 113 entered the cracked portion 100, thereby suppressing sagging due to gravity. The treatment solution for the solid electrolyte layer 113 entered the cracked portion 100, improving the permeability, and thus presumably improving the capacity of the solid electrolytic capacitor 1. The anchor effect of the cracked portion 100 also improves the adhesion between the electrode foil 111 and the solid electrolyte layer 113. As a result, the change rate of the ESR in the high-temperature test was suppressed to 1.2 times.
[0098] On the other hand, the maximum thickness of the solid electrolyte layer of the solid electrolytic capacitor in Comparative Example 1 was 15 μm. The thickness also varied greatly. This is because no cracks were formed, which caused the formation of the solid electrolyte layer to vary. That is, the maximum thickness of the solid electrolyte layer was thicker than that of the solid electrolytic capacitor 1 of the first embodiment. Furthermore, assuming that the capacitance of the solid electrolytic capacitor in the first embodiment is 100, the maximum thickness was about 92.5%. The rate of change in ESR in the high temperature test was 1.5 times.
[0099] Similarly, the maximum thickness of the solid electrolyte layer of the solid electrolytic capacitor in Comparative Example 2 was 20 μm. The thickness also varies greatly. This is presumably because, although cracks were formed, they were formed at equal intervals so as to be parallel to the third face F3 and the fourth face F4, and therefore the influence of the sagging caused by gravity on the processing solution of the solid electrolyte layer 113 could not be suppressed, resulting in the thickness of the solid electrolyte layer varying. That is, the maximum thickness of the solid electrolyte layer was thicker than that of the first embodiment and Comparative Example 1. However, the capacitor capacitance was 100, the same as when the first embodiment was taken as 100. The change rate of ESR in the high temperature test was 1.3 times.
[0100] In this way, by providing the cracks and further having the first region R1 where the cracks are dense and the second region R2 where the cracks are sparse, the adhesion between the electrode foil and the solid electrolyte layer is improved and the thickness of the solid electrolyte layer can be made uniform, compared to when no cracks are provided (Comparative Example 1) and when the cracks are evenly formed (Comparative Example 2). This makes it possible to suppress the rate of change in ESR during high-temperature testing of the solid electrolytic capacitor. This makes it possible to provide a highly reliable solid electrolytic capacitor.
[0101] In the above example, the crack 100 is formed on the first surface F1 and the second surface F2. However, the crack 100 may be formed on only one of the first surface or the second surface F2.
[0102] In the above-described configuration, the cracks 100 are formed only in the porous layer 111L. However, the cracks 100 may be formed in the electrode layer 111F as long as the function of the electrode layer 111F is not affected.
[0103] [Variation 1] Solid electrolytic capacitors 1Ba and 1Bb according to Modification 1 of the present invention will be described with reference to the drawings. Figures 11(A) and 11(B) are cross-sectional views of the solid electrolytic capacitor according to Modification 1.
[0104] 11(A) and 11(B), the solid electrolytic capacitors 1Ba and 1Bb according to Modification 1 are different in structure from the solid electrolytic capacitor 1 according to the first embodiment. Other configurations of the solid electrolytic capacitor according to Modification 1 are similar to those of the solid electrolytic capacitor according to the first embodiment, and descriptions of similar parts will be omitted.
[0105] The solid electrolytic capacitor 1Ba shown in Fig. 11(A) includes a plurality of flat film capacitor elements and a plurality of flat film cathode electrodes. The plurality of capacitor elements and the plurality of cathode electrodes are alternately stacked so that their respective flat film surfaces are parallel to each other and overlap each other in a plan view. In the plurality of flat film capacitor elements, a dielectric layer and a solid electrolyte layer are sequentially formed on the surface of a flat film electrode foil.
[0106] As in the first embodiment, in the electrode foil of the solid electrolytic capacitor 1Ba, a first crack 101 is formed in the first region R1, and a second crack 102 is formed in the second region R2.
[0107] Even with this configuration, in the capacitor element of solid electrolytic capacitor 1Ba, the treatment liquid for the dielectric layer and the solid electrolyte layer penetrates into cracks 100 formed in the electrode foil. Furthermore, more treatment liquid for solid electrolyte layer 113 penetrates into first cracks 101 formed in first region R1 than into second cracks 102 formed in second region R2. That is, the anchor effect of cracks 100 improves the bonding strength between electrode foil 111 and solid electrolyte layer 113. Therefore, the anchor effect of the cracks improves the bonding strength between the electrode foil and the solid electrolyte layer. Furthermore, an electrode foil with improved permeability of the solid electrolyte layer can be formed even in an area where the treatment liquid for the solid electrolyte layer is difficult to sufficiently adhere.
[0108] The solid electrolytic capacitor 1Bb shown in Fig. 11(B) includes a plurality of capacitor elements and external electrodes. The plurality of flat-film capacitor elements are formed by sequentially forming an electrode foil, a dielectric layer, a solid electrolyte layer, a carbon layer, and a metal layer. The plurality of capacitor elements are stacked to form a laminate. The laminate is sealed with resin to form a sealing body.
[0109] The external electrode has one end and the other end, the one end of the external electrode is sandwiched in the stacking direction of the plurality of capacitor elements, and the other end is disposed so as to abut against a side surface and a bottom surface of the sealing body.
[0110] As in the first embodiment, in the electrode foil of the solid electrolytic capacitor 1Bb, a first crack 101 is formed in the first region R1, and a second crack 102 is formed in the second region R2.
[0111] Even with this configuration, in the capacitor element of solid electrolytic capacitor 1Bb, the treatment liquid for the dielectric layer and the solid electrolyte layer penetrates into cracks 100 formed in the electrode foil. Furthermore, more treatment liquid for solid electrolyte layer 113 penetrates into first cracks 101 formed in first region R1 than into second cracks 102 formed in second region R2. That is, the anchor effect of cracks 100 improves the bonding strength between electrode foil 111 and solid electrolyte layer 113. Therefore, the anchor effect of the cracks improves the bonding strength between the electrode foil and the solid electrolyte layer. Furthermore, an electrode foil with improved permeability of the solid electrolyte layer can be formed even in an area where the treatment liquid for the solid electrolyte layer is difficult to adhere sufficiently.
[0112] [Variation 2] A capacitor element 11C according to Modification 2 of the present invention will be described with reference to Fig. 12. Fig. 12 is an enlarged view of a portion of the capacitor element according to Modification 2.
[0113] 12, capacitor element 11C according to Modification 2 has a different structure of the cracked portion from capacitor element 11 of solid electrolytic capacitor 1 according to the first embodiment. Other configurations of the solid electrolytic capacitor according to Modification 2 are similar to those of the solid electrolytic capacitor according to the first embodiment, and descriptions of similar parts will be omitted.
[0114] 12, a predetermined number of cracks 100C are formed in capacitor element 11C. Cracks 101C are formed in first region R1 on the surface (first face F1) of electrode foil 111, and cracks 102C are formed in second region R2.
[0115] In the first embodiment, an example in which the crack 100 is formed continuously (straight line) is shown. On the other hand, in the example shown in Fig. 12, the crack 100C is formed in a dashed line. In other words, the crack 100C is formed discontinuously.
[0116] Even with this configuration, in capacitor element 11C, the treatment liquid for the dielectric layer and the solid electrolyte layer penetrates into cracks 100C formed in the electrode foil. Furthermore, more treatment liquid for solid electrolyte layer 113 penetrates into first cracks 101C formed in first region R1 than into second cracks 102C formed in second region R2. That is, the anchor effect of cracks 100C improves the bonding strength between electrode foil 111 and solid electrolyte layer 113. Therefore, the anchor effect of the cracks improves the bonding strength between the electrode foil and the solid electrolyte layer. Furthermore, an electrode foil with improved permeability of the solid electrolyte layer can be formed even in an area where the treatment liquid for the solid electrolyte layer is difficult to sufficiently adhere.
[0117] [Variation 3] A capacitor element 11D according to Modification 3 of the present invention will be described with reference to Fig. 13. Fig. 13 is an enlarged view of a portion of the capacitor element according to Modification 3.
[0118] 13, capacitor element 11D according to Modification 3 has a different structure of the cracked portion from capacitor element 11 of solid electrolytic capacitor 1 according to the first embodiment. Other configurations of the solid electrolytic capacitor according to Modification 3 are similar to those of the solid electrolytic capacitor according to the first embodiment, and descriptions of similar parts will be omitted.
[0119] 13, a predetermined number of cracks 100D are formed in capacitor element 11D. The predetermined number of cracks 100D are continuously formed across first face F1, fifth face F5, second face F2, and sixth face F6. In other words, cracks 100D are formed in a spiral shape across first face F1, fifth face F5, second face F2, and sixth face F6.
[0120] A crack 101D is formed in a first region R1 of the surface (first face F1) of the electrode foil 111, and a crack 102D is formed in a second region R2.
[0121] Even with this configuration, in capacitor element 11D, the treatment liquid for the dielectric layer and the solid electrolyte layer penetrates into cracks 100D formed in the electrode foil. Furthermore, more treatment liquid for solid electrolyte layer 113 penetrates into first cracks 101D formed in first region R1 than into second cracks 102D formed in second region R2. That is, the anchor effect of cracks 100D improves the bonding strength between electrode foil 111 and solid electrolyte layer 113. Therefore, the anchor effect of the cracks improves the bonding strength between the electrode foil and the solid electrolyte layer. Furthermore, an electrode foil with improved permeability of the solid electrolyte layer can be formed even in an area where the treatment liquid for the solid electrolyte layer is difficult to sufficiently adhere.
[0122] [Variation 4] A capacitor element 11E according to Modification 4 of the present invention will be described with reference to Fig. 14. Fig. 14 is an enlarged view of a portion of the capacitor element according to Modification 4.
[0123] 14, capacitor element 11E according to Modification 4 has a different structure of the cracked portion from capacitor element 11 according to the first embodiment. Other configurations of the solid electrolytic capacitor according to Modification 4 are similar to those of the solid electrolytic capacitor according to the first embodiment, and therefore descriptions of similar parts will be omitted.
[0124] 14, a predetermined number of cracks 100E are formed in capacitor element 11E. Cracks 101E are formed in first region R1 on the front surface (first face F1) of electrode foil 111.
[0125] In the first embodiment, an example was shown in which the crack 100 is formed in the first region R1 and the second region R2. On the other hand, in the example shown in Fig. 14, the crack 101E is formed only in the first region R1. In other words, no crack is formed in the second region R2. That is, the second density is zero.
[0126] Even with this configuration, in capacitor element 11E, the treatment liquid for the dielectric layer and the solid electrolyte layer penetrates into crack 100E (first crack 101E formed in first region R1) formed in the electrode foil. That is, the anchor effect of crack 100E improves the bonding strength between electrode foil 111 and solid electrolyte layer 113. The anchor effect of the crack also improves the bonding strength between the electrode foil and solid electrolyte layer. Therefore, by forming crack 101E at least in first region R1 where the treatment liquid is unlikely to adhere sufficiently due to the effect of gravity, electrode foil 111 with improved permeability of solid electrolyte layer 113 can be formed.
[0127] Furthermore, the configurations and various modified examples shown in the above-described embodiments can be combined as appropriate, and effects according to each combination can be achieved.
[0128] The correspondence between the configuration according to the present invention and the above-mentioned configuration will be described below.
[0129] [Note] <1> a capacitor element including: an anode body in the form of a flat membrane, the anode body including a valve metal and a porous layer having a plurality of holes on a surface of the valve metal; a dielectric layer formed on at least a cathode-forming region; and a solid electrolyte layer formed on the dielectric layer, the anode body having an anode terminal region in which the solid electrolyte layer is not formed; and the cathode-forming region in which the solid electrolyte layer is formed; Equipped with the cathode region in the anode body has a first region on a surface thereof and a second region adjacent to the first region; A predetermined number of cracks are formed in the first region and the second region, Among the predetermined number of cracks, a first density occupied by first cracks formed in the first region is greater than a second density occupied by second cracks formed in the second region. Capacitor element.
[0130] <2> The first density and the second density are The number of the first cracks and the second cracks is determined according to the number of the first cracks and the second cracks. <1> The capacitor element according to claim 1 .
[0131] <3> The first density and the second density are Determined according to the depth at which the first crack portion and the second crack portion are formed. <1> The capacitor element according to claim 1 .
[0132] <4> In plan view, the first region is formed at a position adjacent to the anode terminal region, The second region is formed in the cathode formation region. <1> The capacitor element according to claim 1 .
[0133] <5> In plan view, The first region is formed in the center of the cathode formation region, The second region is formed so as to surround a part of the first region. <1> The capacitor element according to claim 1 .
[0134] <6> The solid electrolyte layer is formed so as to fill the predetermined number of cracks. <1> The capacitor element according to claim 1 .
[0135] <7> the solid electrolyte layer comprises an inner solid electrolyte layer and an outer solid electrolyte layer, the predetermined number of cracks are formed so that the inner solid electrolyte layer penetrates into the cracks, <1> The capacitor element according to claim 1 .
[0136] <8> The predetermined number of cracks are cracks formed in stripes. <1> ~ <7> 2. The capacitor element according to claim 1 .
[0137] <9> <1> ~ <8> The capacitor element according to any one of the preceding claims, a sealing body that seals a laminate in which a plurality of the capacitor elements are laminated with an insulating resin; a first external electrode connected to an end of the anode terminal region; A second external electrode connected to the cathode formation region; Equipped with Solid electrolytic capacitor.
[0138] <10> a capacitor element forming step of forming a capacitor element having an anode body in the form of a flat membrane having a porous layer containing a valve metal and having a plurality of holes on a surface of the valve metal, a dielectric layer formed on at least a cathode formation region, and a solid electrolyte layer formed on the dielectric layer, the capacitor element having an anode terminal region in which the solid electrolyte layer is not formed in the anode body, and the cathode formation region in which the solid electrolyte layer is formed; a first external electrode forming step of forming a first external electrode connected to an end portion of the anode terminal region; a second external electrode forming step of forming a second external electrode connected to the cathode formation region; a sealing body forming step of laminating a plurality of the capacitor elements and sealing them with an insulating resin to form a sealing body having a first surface from which an end of the anode terminal region is linearly exposed; Equipped with The capacitor element forming step includes: In a first region on the surface of the anode body and in a second region adjacent to the first region, forming a predetermined number of cracks in the first region and the second region; A first density occupied by the first cracks formed in the first region is formed to be larger than a second density occupied by the second cracks formed in the second region. A method for manufacturing a solid electrolytic capacitor.
[0139] <11> The predetermined number of cracks is by applying pressure to the surface such that the pressure applied to the first region of the anode body is greater than the pressure applied to the second region of the anode body. <10> 2. A method for producing the solid electrolytic capacitor according to claim 1 . [Explanation of symbols]
[0140] d1,d2...depth F1…Front page F2…Second side F3…Side 3 F4…Fourth side F5…Side 5 F6…Side 6 R1…first area R2…Second area 1,1A,1Ba,1Bb...Solid electrolytic capacitors 10...Capacitor assembly 11, 11A, 11C, 11D, 11E...Capacitor elements 19...Conductive material 20…First external electrode 30…Second external electrode 40...Insulating resin body 50...Conductive adhesive 100, 100A, 100C, 100D, 100E...Cracked part 101, 101A, 101C, 101D, 101E...First crack 102, 102A, 102C, 102D...Second crack 111...Electrode foil 111F…electrode layer 111L…Porous layer 112...Dielectric layer 113...Solid electrolyte layer 114…Carbon layer 115...Metal layer 400...Sealing body 401…Top 402…Bottom 403...Side 1 404…Second side
Claims
1. a capacitor element including: an anode body in the form of a flat membrane, the anode body including a valve metal and a porous layer having a plurality of holes on a surface of the valve metal; a dielectric layer formed on at least a cathode-forming region; and a solid electrolyte layer formed on the dielectric layer, the anode body having an anode terminal region in which the solid electrolyte layer is not formed; and the cathode-forming region in which the solid electrolyte layer is formed; Equipped with the cathode region in the anode body has a first region on a surface thereof and a second region adjacent to the first region; a predetermined number of cracks are formed in the first region and the second region, Among the predetermined number of cracks, a first density occupied by first cracks formed in the first region is greater than a second density occupied by second cracks formed in the second region. Capacitor element.
2. The first density and the second density are The capacitor element according to claim 1 , wherein the number of the first cracks and the number of the second cracks are determined according to the number of the first cracks and the second cracks.
3. The first density and the second density are The capacitor element according to claim 1 , wherein the depth is determined according to the depth at which the first crack and the second crack are formed.
4. In plan view, the first region is formed at a position adjacent to the anode terminal region, The capacitor element according to claim 1 , wherein the second region is formed in the cathode forming region.
5. In plan view, The first region is formed in the center of the cathode formation region, The capacitor element according to claim 1 , wherein the second region is formed so as to surround a portion of the first region.
6. The capacitor element according to claim 1 , wherein the solid electrolyte layer is formed so as to fill the predetermined number of cracks.
7. the solid electrolyte layer comprises an inner solid electrolyte layer and an outer solid electrolyte layer, the predetermined number of cracks are formed so that the inner solid electrolyte layer penetrates into the cracks, The capacitor element according to claim 1 .
8. The predetermined number of cracks are cracks formed in stripes. The capacitor element according to claim 1 .
9. The capacitor element according to any one of claims 1 to 7, a sealing body that seals a laminate in which a plurality of the capacitor elements are laminated with an insulating resin; a first external electrode connected to an end of the anode terminal region; a second external electrode connected to the cathode forming region; Equipped with Solid electrolytic capacitor.
10. a capacitor element forming step of forming a capacitor element having an anode body in the form of a flat membrane having a porous layer containing a valve metal and having a plurality of holes on a surface of the valve metal, a dielectric layer formed on at least a cathode formation region, and a solid electrolyte layer formed on the dielectric layer, the capacitor element having an anode terminal region in which the solid electrolyte layer is not formed in the anode body, and the cathode formation region in which the solid electrolyte layer is formed; a first external electrode forming step of forming a first external electrode connected to an end portion of the anode terminal region; a second external electrode forming step of forming a second external electrode connected to the cathode formation region; a sealing body forming step of laminating a plurality of the capacitor elements and sealing them with an insulating resin to form a sealing body having a first surface from which an end of the anode terminal region is linearly exposed; Equipped with The capacitor element forming step includes: In a first region on the surface of the anode body and in a second region adjacent to the first region, forming a predetermined number of cracks in the first region and the second region; A first density occupied by the first cracks formed in the first region is formed to be larger than a second density occupied by the second cracks formed in the second region. A method for manufacturing a solid electrolytic capacitor.
11. The predetermined number of cracks is The method for producing a solid electrolytic capacitor according to claim 10 , wherein the solid electrolytic capacitor is formed by applying pressure to the surface such that the pressure applied to the first region of the anode body is greater than the pressure applied to the second region.
Citation Information
Patent Citations
Chopper controlled electric motor vehicle
JP1983058802A
Solid electrolytic capacitor element, and solid electrolytic capacitor and method for manufacturing same
WO2022009800A1